As pedagogias do aprender a aprender e algumas ilusões da assim chamada sociedade do conhecimento - Newton Duarte (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
This article considers the pedagogy of competencies as one of the pedagogies of learning to learn and presents four valuational propositions contained in the slogan learning to learn: 1) learning which occurs without the transmission of knowledge by someone is the most desirable; 2) the method by which knowledge is constructed is more important than that knowledge already socially produced; 3) student activities should be inspired by the needs and interests of the individual; 4) education ought to prepare individuals for a constant process of adaptation and readaptation to a society in accelerated process of change. The article defends the position that the learning to learn pedagogies belong to an ideological universe charged with illusions about the socalled knowledge society and concludes by presenting five of these illusions.